Multivariate characterization of salt and fat content, and the fatty acid profile of pastry and bakery products - Albuquerque, T.G. (2018)
Bakery and pastry products are highly appreciated worldwide. Due to consumer demand, a wide diversity of this type of food is available all over the world. The aim of this study was to evaluate the content of salt, fat and fatty acids in the composition of 91 bakery and pastry products commercialised in Portugal. Moreover, a detailed comparison between commercial and supermarket brands of similar foods, as well as between foods with or without gluten was performed. The obtained results allowed us to conclude that most of the analysed foods have a high percentage of saturated fatty acids. Also, considerable amounts of salt were determined, while the trans fatty acid content in the analysed foods was in general low (<0.5%). Moreover, differences in the salt content higher than 6-fold between brands of the same type of foodstuff were observed, which should be considered at the moment of choice. This fact proves that it is possible to produce similar foods which are healthier with better nutritional quality. Since this type of food is highly appreciated by people of all ages, but mostly by children and young people, it is of utmost importance to implement strategies and establish goals, to improve their nutritional quality.